An international multidisciplinary consensus statement on MAFLD and the risk of CVD - YILMAZ, YUSUF (My University, 2023)
Background: Fatty liver disease in the absence of excessive alcohol consumption is an increasingly common condition with a global prevalence of ~ 25–30% and is also associated with cardiovascular disease (CVD). Since systemic metabolic dysfunction underlies its pathogenesis, the term metabolic (dysfunction)-associated fatty liver disease (MAFLD) has been proposed for this condition. MAFLD is closely intertwined with obesity, type 2 diabetes mellitus and atherogenic dyslipidemia, which are established cardiovascular risk factors. Unlike CVD, which has received attention in the literature on fatty liver disease, the CVD risk associated with MAFLD is often underestimated, especially among Cardiologists. Methods and results: A multidisciplinary panel of fifty-two international experts comprising Hepatologists, Endocrinologists, Diabetologists, Cardiologists and Family Physicians from six continents (Asia, Europe, North America, South America, Africa and Oceania) participated in a formal Delphi survey and developed consensus statements on the association between MAFLD and the risk of CVD. Statements were developed on different aspects of CVD risk, ranging from epidemiology to mechanisms, screening, and management. Conculsions: The expert panel identified important clinical associations between MAFLD and the risk of CVD that could serve to increase awareness of the adverse metabolic and cardiovascular outcomes of MAFLD. Finally, the expert panel also suggests potential areas for future research.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; GASTROENTEROLOJİ VE HEPATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; GASTROENTEROLOGY & HEPATOLOGY; Hepatoloji; Hepatology; Cardiovascular disease; Consensus; Delphi survey; MAFLD; Metabolic (dysfunction)-associated fatty liver disease; Non-alcoholic fatty liver disease; Metabolic (dysfunction); associated fatty liver disease; MAFLD; Non-alcoholic fatty liver disease; Cardiovascular disease; Consensus; Delphi survey